The influence of language proficiency on job performance of media journalists in northern region on Malaysia - Tan, Guan Cheong; Ab Hamid, Kamal (2017)
The main purpose of this study is to examine the influence of language proficiency on the job performance of media journalists in the northern region of Peninsular Malaysia which comprising of Kedah, Perlis and Penang.The respondents will be journalists from the print media organisations in these states.The study is more focus on English language proficiency of media journalists in the three state. For decades, the language issues still cannot be addressed which prompt the researcher to conduct the study.The implications of poor language proficiency among journalists will resulted in journalists unable to understand the issues, missed quoting, careless grammatical mistakes, time consuming in clearing stories, late finish of works, increase workload, stress and declining of job performance of journalists. It is trend now editors clear stories to improve reporters’ language all the time.The findings of this study may allow educational policy planners, academicians, teachers to optimise English learning programmes to improve the language proficiency, language ability and language skills of students and universities graduates who will be the future main workforce of the country.